DETERMINAN KEPUTUSAN HEDGING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA PADA TAHUN 2013-2014 - Kadek Indah Estyari; Budi Santoso; I Nyoman Nugraha Ardana Putra (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The purpose of this study was to determine the factors that influence the company's decision to hedge on manufacturing industry companies in the 2013-2014 period. The type of data used in this study is secondary data with data collection techniques using the documentation method. Determination of the sample in this study using purposive sampling method with certain criteria so as to obtain 114 samples. The analytical technique used in this study is logistic regression analysis. The results of this study indicate that: (1) Leverage has no significant effect on hedging decisions. (2) Firm size has a significant effect on hedging decisions. (3) Profitability has a significant effect on hedging decisions. (4) Liquidity has a significant effect on hedging decisions